The role of ZnO in TeO2 thin films for optical and radiation dosimetry applications - Mustapha, Idris M.; Matthew, Kolo T.; Oyeleke, Olarinoye I.; Sharifat, Ibrahim; Abdul Karim, Muhammad K.; Paiman, Suriati (Elsevier, 2025)
The role of doping a p-type TeO2 film with an n-type ZnO on its optical and X-ray dosimetric properties was investigated by experiments using (ZnO)x(TeO2)1-x thin films (x = 0, 0.2, and 0.4 wt%). The physicochemical, optical, and electrical properties of (ZnO)x(TeO2)1-x thin films grown on a soda-lime glass substrate by spray pyrolysis were studied. The XRD study revealed a polycrystalline structure of the films and weak diffraction peaks belonging to paratellurite TeO2 in all film samples. A peak shift was observed in (ZnO)0.2(TeO2)0.8 and (ZnO)0.4(TeO2)0.6, indicating the presence of ZnO in the TeO2 crystal lattice. The FESEM image revealed the grain size and roughness of the films, which decrease with increasing ZnO concentration. The film thickness determined by cross-sectional FESEM images are 14.00, 14.11, and 12.12 μm for TeO2, (ZnO)0.2(TeO2)0.8, (ZnO)0.4(TeO2)0.6, respectively. The UV–Vis study revealed high transparency in the visible light regions and a slight decrease in band gap values as ZnO concentration increased. The FTIR study showed resonances corresponding to the symmetrical equatorial and asymmetrical axial stretching frequencies of the Te-O bonds and a stretching mode of a Zn-O bond. Raman spectra detected the existence of Raman-active modes of TeO2 for all films and ZnO in the ZnO-doped TeO2 thin film samples. The current-voltage characteristics technique, which investigates the behaviour of electrical properties, was used to measure the change in current as a function of X-ray radiation dose. The I-V characteristics showed increased induced current at 100 and 200 cGy/min dose rates for all film samples. Consequently, we confirmed that the physicochemical properties of TeO2 films could be improved by ZnO doping at a 40 % wt% concentration for maximum dose response and high transparency. These thin films have high sensitivity and can detect both low and high-energy radiation, making them useful in various radiation-related applications such as medical dosimetry, environmental monitoring, and radiation safety. TeO₂'s superior optical properties are enhanced by ZnO's wide bandgap high exciton binding energy, and radiation sensitivity making it a competitive candidate for the development of miniaturized thin-film dosimeter that can fit in portable gadgets such as smartphones.